2022
DOI: 10.3389/fimmu.2022.935160
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Pathogenesis of Acute-On-Chronic Liver Failure and the Danger Hypothesis

Abstract: Acute-on-chronic liver failure (ACLF) is a group of clinical syndromes related to severe acute liver function impairment and multiple-organ failure caused by various acute triggering factors on the basis of chronic liver disease. Due to its severe condition, rapid progression, and high mortality, it has received increasing attention. Recent studies have shown that the pathogenesis of ACLF mainly includes direct injury and immune injury. In immune injury, cytotoxic T lymphocytes (CTLs), dendritic cells (DCs), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…While the “three-hit” and “second-hit” hypothesis 15 , 16 explain aspects of liver failure, cytokine storms play a crucial role in its development 17 , 18 . IL-6, a key inflammatory cytokine, regulates T-cell activation, differentiation, and hepatocyte regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…While the “three-hit” and “second-hit” hypothesis 15 , 16 explain aspects of liver failure, cytokine storms play a crucial role in its development 17 , 18 . IL-6, a key inflammatory cytokine, regulates T-cell activation, differentiation, and hepatocyte regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…During immune injury, cytotoxic T lymphocytes (CTL), dendritic cells (DC), and CD4 + T cells amass in the liver tissue at the very start and subsequently secrete diverse pro-in ammatory cytokines and chemokines, conversely recruiting more immune cells to the liver. Changes in the immune microenvironment cause liver immune injury under the interaction of immune cells and cytokines, which leads to massive liver cell necrosis, mitochondrial destruction, and, eventually, liver failure [38][39][40]. In a clinical cohort of multiple liver diseases, including HBV-ACLF, acute-on-chronic hepatic dysfunction (ACHD), liver cirrhosis (LC), or chronic hepatitis B (CHB), the PBMC transcriptome sequencing results showed that immune dysregulation was the most remarkable and pernicious feature that further leads to the development of HBV infection, CHB, or LC into ACHD and ACLF, with signi cantly upregulated signals of neutrophil-and monocyte-related pathways and downregulated signals related to adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, preventing and eliminating ALI has become an urgent issue to be solved globally. At present, epigenetics, oxidative stress, inflammatory immunity and other pathological mechanisms have been confirmed to be widely involved in the abnormal activities of hepatocytes and inflammatory immune cells and metabolism-induced ALI, and promising targets and potential therapeutic strategies have also been hotly discussed ( 79 ). Meanwhile, the role of gut microbiota in ALI has become increasingly prominent and has gradually attracted attention ( 80 ).…”
Section: Targeting Gut Microbiota For Acute Liver Injurymentioning
confidence: 99%